2011
DOI: 10.1007/s11482-011-9158-2
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Changes in Well-Being Following Polysaccharide Intake in Middle-Aged Adults

Abstract: Objectives: There is increased scientific interest in the effects of nutrition on cognition and well-being. Plant sourced polysaccharides play multiple roles in the biological processes required for health and well-being. This study explored the subjective experiential reports of well-being following intake of a plant derived polysaccharide supplement.Design: The study used a 12 week double-blind, placebo controlled polysaccharide supplementation design.Method: 109 middle-aged adults (45-60 years) took a stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The protective effects of vegetables and fruits might be attributed to nutrients, such as carbohydrates, vitamins, antioxidants, and phytochemicals [5]. The possible association of carbohydrates contained in such foods with psychological health may be due to the secretion of insulin caused by consumption of these foods, which consequently stimulated the production of neurotransmitters such as serotonin by the entry of tryptophan into the brain [42][43][44]. Furthermore, the nutrients in vegetables and fruits, including folate and vitamin B6 [45], antioxidants (such as vitamins C, E) [18], phytochemicals (such as polyphenols) [18,46], and minerals (such as iron, calcium and magnesium) [47] could have a protective role against the psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effects of vegetables and fruits might be attributed to nutrients, such as carbohydrates, vitamins, antioxidants, and phytochemicals [5]. The possible association of carbohydrates contained in such foods with psychological health may be due to the secretion of insulin caused by consumption of these foods, which consequently stimulated the production of neurotransmitters such as serotonin by the entry of tryptophan into the brain [42][43][44]. Furthermore, the nutrients in vegetables and fruits, including folate and vitamin B6 [45], antioxidants (such as vitamins C, E) [18], phytochemicals (such as polyphenols) [18,46], and minerals (such as iron, calcium and magnesium) [47] could have a protective role against the psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed link is that insulin, triggered through the consumption of carbohydrates, can increase entry of tryptophan in the brain, which in turn stimulates the synthesis of important neurotransmitters including serotonin ( 9 ) . Although evidence has indicated that the ingestion of simple carbohydrates, present in refined sugary products, may result in temporal improvements in mood ( 17 ) , it has been suggested that complex carbohydrates provide a longer lasting effect due to their slower release of glucose ( 18 , 19 ) . Complex carbohydrates are particularly prevalent in low glycaemic index foods including certain types of FV (e.g.…”
Section: How Might Fruit and Vegetables And Psychological Well-being mentioning
confidence: 99%
“…Prior studies involving the glyconutrient Ambrotose have noted positive outcomes when assessing various surrogate markers of health. For example, Ambrotose glyconutrients have been associated with improvements in memory and subjective ratings of well-being in numerous studies [4,5,15,16]. With regards to immune modulation, marathon runners ingesting Advanced Ambrotose daily for 15 days prior to competition exhibited lower resting salivary chemokines, Gro-alpha and Gro-beta, compared to nonsupplemented counterparts; however, supplemented runners did not experience a reduction in these markers after exercise but did experience a reduction in the salivary chemokine, angiogenin, after exercise [17].…”
Section: Discussionmentioning
confidence: 99%